THE ROLE OF MODERN PEDAGOGICAL TECHNOLOGIES IN TEACHING THE SUBJECT OF THERAPY (Modern education and development, 2025)
The article considers the role of modern pedagogical technologies in teaching the subject of therapy in medical education. The main types of pedagogical technologies such as interactive teaching methods, e-learning and multimedia resources are analysed. It is emphasised that the use of these technologies helps to increase student motivation, individualise learning and develop critical thinking. The benefits of integrating theoretical knowledge and practical skills as well as the impact of distance learning in the context of modern challenges are also discussed. The article highlights the problems and challenges faced by teachers in implementing new technologies, such as the need for training and technical limitations. In conclusion, it is emphasised that the successful application of modern pedagogical technologies in teaching therapy is a key factor in improving the quality of medical education and training highly qualified specialists.